2011
DOI: 10.1111/j.1439-0485.2011.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity influences cold‐seep macrofaunal communities within and among seeps along the Norwegian margin – Part 2: contribution of chemosynthesis and nutritional patterns

Abstract: The relative contribution of chemosynthesis in heterotrophic fauna at seeps is known to be influenced by depth and by habitat. Using stable isotopes of carbon and nitrogen, we investigated macro‐ and megafaunal nutritional patterns in Norwegian margin cold seeps by comparing food webs both among habitats within a seep site and between different sites. The very active Håkon Mosby mud volcano (HMMV) is characterized by geochemical gradients, microbial activity and faunal zonation from the centre to the periphery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…VR3. Tanaid crustaceans are commonly observed in deep‐sea macrobenthos (Bluhm et al ) and have previously been identified at deeper shelf systems around Svalbard (Włodarska‐Kowalczuk et al ; Soltwedel et al ) and cold seep environments along the Norwegian shelf (Blazewicz‐Paszkowycz and Bamber ; Decker and Olu ). Tanaidacea can exploit both chemo‐, and photo‐autotrophic energy sources and have been suggested to feed on microbial mats, (Sellanes et al ; Levin et al ), which offer alternative food resources during periods of low organic matter input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR3. Tanaid crustaceans are commonly observed in deep‐sea macrobenthos (Bluhm et al ) and have previously been identified at deeper shelf systems around Svalbard (Włodarska‐Kowalczuk et al ; Soltwedel et al ) and cold seep environments along the Norwegian shelf (Blazewicz‐Paszkowycz and Bamber ; Decker and Olu ). Tanaidacea can exploit both chemo‐, and photo‐autotrophic energy sources and have been suggested to feed on microbial mats, (Sellanes et al ; Levin et al ), which offer alternative food resources during periods of low organic matter input.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute these differences to the methane activity at the cold seep. Four of the top five infaunal taxa at VR seeps (Table ) are recognized from reduced environments including cold seeps (Dubilier et al ; Blazewicz‐Paszkowycz and Bamber ; Decker and Olu ). The most numerically dominant taxa among these is Tanaidacea that occurred en masse at Sta.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge is mostly based on measurements of the stable C isotope ratio of faunal bulk tissue [5], [9], [31], [32]. At cold seeps, both methane and its oxidation product CO 2 , are strongly depleted in 13 C [33].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of sample collection, bacterial mats were visible in still images across the Oman margin from depths of 1000 to 3300 m, colonising both single jellyfish and jelly detritus (Billett et al, 2006). Sulfuroxidising bacteria at cold seeps are characterised by depleted δ 15 N signatures (Decker and Olu, 2011;Demopoulos et al, 2010;Levin and Michener, 2002). We do not have isotopic data for bacteria from the Oman margin, but bacteria from the Pakistan margin had δ 15 N values ranging from −0.4 to 11.9 ‰, including Thioploca sp., which had a δ 15 N value of −0.1 ‰.…”
Section: Inter-margin Differencesmentioning
confidence: 99%